2021
DOI: 10.4018/978-1-7998-8231-2.ch026
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of COVID-19 on Tourism and Hospitality Employment

Abstract: This chapter attempts to draw attention to the effects of COVID-19 on tourism and hospitality employment. Specifically, two major impacts on the workforce are detected and discussed within this scope: job losses and deterioration of the working conditions. Job loss causes financial strain, deterioration of physical and psychological health, and social consequences for the dismissed individuals. In addition, employees who remain in the organizations also face negative impacts of the COVID-19 crisis such as heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 66 publications
0
0
0
Order By: Relevance
“…Regarding travel restrictions, social measures, lockdowns, and public health concerns, tourism firms experience a significant decline in their customers and revenue [114]. Therefore, restructuring and downsizing became a necessary response for companies in order to align with the reduced demand in the tourism industry [115].…”
Section: The Structural Capital Of Tourism-related Firms In Thailandmentioning
confidence: 99%
“…Regarding travel restrictions, social measures, lockdowns, and public health concerns, tourism firms experience a significant decline in their customers and revenue [114]. Therefore, restructuring and downsizing became a necessary response for companies in order to align with the reduced demand in the tourism industry [115].…”
Section: The Structural Capital Of Tourism-related Firms In Thailandmentioning
confidence: 99%
“…Giousmpasoglou et al (2020) identified the challenges faced by hospitality managers in managing cash flow, layoffs, and changing consumer behaviors. Karsavuran (2021) emphasized the importance of government support to promote economic recovery in the tourism and hospitality industry. Susanto et al (2021) found that the Covid-19 pandemic had a negative impact on travel intention, leading individuals to prioritize health and safety concerns and domestic travel over international travel.…”
Section: Post-pandemic Risksmentioning
confidence: 99%
“…Overall, Kristiana et al's (2021) article emphasized the importance of adaptation and innovation in the tourism industry during the pandemic and the strate-gies implemented by stakeholders to mitigate its impact. The study by Guerriero et al (2020) highlighted the need to integrate health and sustainability considerations into post-pandemic economic policies, while Karsavuran's (2021) research stressed the importance of government support in retaining employees and promoting economic recovery in the tourism and hospitality industry. Biå et al (2020) proposed that international management system standards can provide a valuable framework for developing an integrated plan to ensure business continuity in the post-pandemic period.…”
Section: Post-pandemic Risksmentioning
confidence: 99%